Assessment of the nutritional, sociodemographic and socioeconomic status of people living with HIV/AIDS treated in a reference hospital in the Northern region of Brazil (Research, Society and Development, 2023)
People living with HIV-1/AIDS (PLWHA) have several opportunistic diseases and comorbidities resulting from the immunosuppressive alterations that take place in these individuals. The wide spread and rapid progress of the syndrome demonstrate that the pandemic affects individuals of different age groups and social levels. Objective: To describe the nutritional, socioeconomic and demographic profile of PLWHA treated at a referral hospital for infectious and parasitic diseases (IPD) in the Northern Region of Brazil. Methods: Type of descriptive, prospective, cross-sectional and quantitative study, with a sample of 80 patients of both sexes aged between 18 and 59 years. Attended at the Specialized Care Service (SAE) of the João de Barros Barreto University Hospital (HUJBB/UFPA). A protocol was used for data collection containing socioeconomic and sociodemographic variables. To assess the nutritional status, the Body Mass Index (BMI) and Arm Circumference (BC) were used. Results: The nutritional profile, according to BMI, showed a prevalence of overweight. However, BC showed eutrophy in 57.5% and malnutrition in 32.50% of those evaluated. In the researched group, there was a predominance of males (63.75%), self-declaring to be brown (61.25%), with complete high school (33.75%) and living in their own brick house. Regarding the socioeconomic profile, most patients have their own home. Conclusion: It is therefore necessary, in all phases of the treatment of PLWHA, an effective nutritional care plan that safeguards their nutritional improvement and consequently their quality of life.